Nonsurgical Treatment of Keloids and Hypertrophic Scars - Saddawi-Konefka, Robert; Watson, Deborah (Facial Plastic Surgery, 2019)
Despite the ubiquitous nature of scar tissue, there is not a single, reliable strategy to prevent or treat excessive scarring. The difficulty in arriving at a universally accepted form of management is multifaceted: there is an incomplete understanding of the complex pathophysiology of scar formation; a lack of common metrics hampers the accurate description of scar quality and characteristics; model systems do not exist for proper investigation in the controlled environment of a laboratory; and there is only limited data from prospective, randomized controlled clinical trials. Accordingly, the management of cutaneous scars is typically based upon the experience from practitioners rather than from evidence-based data. This article will review the pathophysiology of excessive scar formation, define the most common scars—hypertrophic scars and keloids—and discuss the evidence to support the current nonsurgical therapies in use to both prevent and treat excessive scars.
Keywords: keloid; hypertrophic scar; excessive scar